KEJAHATAN TRANSNASIONAL MELALUI PERDAGANGAN BARTER NARKOBA DI KAWASAN PERBATASAN RI – PAPUA NEW GUINEA - Sinaga, Melpayanty (Masyarakat Indonesia, 2020)
The purpose of this research is to analyze the transnational crime in the border of RI – Papua New Guinea. Transnational crime through the barter of drugs and motorcycle become trend and new crime in Jayapura. In the general, the transnational crime often happen with an exchange of money with drugs, but in this case is becoming unique with the exchange motorcycles through the cross of state. This research is using mix method by qualitative and quantitative. The technique of collection data using depth interview to the actors such as the representative state which is known as security forces, the victims, and also doing survey to the location of drugs trafficking by sea and land. The result of this research found that the barter of drugs with motorcycle is becoming increased because of the less controlling of security and also the post –post of the borders is not build and it makes the perpetrators send illegal drugs by narrow streets or alleyways which cannot be detected by security officers and other side Papua know as the place of surround by sea. It caused the perpetrators very easy to do drugs trafficking.